The ‘Singapore Fever’ in China: policy mobility and mutation - Lim, Kean Fan; Horesh, Niv (Cambridge University Press, 2016)
The ‘Singapore Model’ has constituted the only second explicit attempt by the Communist Party of China (CPC) to learn from a foreign country following Mao Zedong’s pledge to contour ‘China’s tomorrow’ on the Soviet Union experience during the early 1950s. This paper critically evaluates policy transfers from Singapore to China in the post-Mao era. It re-examines how this Sino-Singaporean regulatory engagement came about historically following Deng Xiaoping’s visit to Singapore in 1978, and offers a careful re-reading of the degree to which actual policy borrowing by China could transcend different state ideologies, abstract ideas and subjective attitudes. Particular focus is placed on the effects of CPC cadre training in Singapore universities and policy mutation within two government-to-government projects, namely the Suzhou Industrial Park and the Tianjin Eco-City. The paper concludes that the ‘Singapore Model’, as applied in post-Mao China, casts institutional reforms as an open-ended process of policy experimentation and adaptation that is fraught with tension and resistance.